Adam Shapley correspondence - Shapley, Adam, -1781.
ALS (New London, Conn.) written by Shapley requesting funds for his troops.
Continental Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Continental Army; Connecticut -- History -- Revolution, 1775-1783.; New London (Conn.) -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783.; Army officers